2022
DOI: 10.1007/s12325-022-02149-7
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Sequelae and Quality of Life in Adults with Meningococcal Meningitis: Lessons from the COMBAT Multicentre Prospective Study

Abstract: Introduction COMBAT is a prospective, multicentre cohort study that enrolled consecutive adults with community-acquired bacterial meningitis (CABM) in 69 participating centres in France between February 2013 and July 2015 and followed them for 1 year. Methods Patients aged at least 18 years old, hospitalised with CABM were followed during their hospitalisation and then contacted by phone 12 months after enrolment. Here we present the prevalence of sequelae at 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Higher rates (11.6%) were reported in adult cases with N. meningitidis purpura fulminans [47]. In the same way, a prospective observational study found that 34.3% of adult cases had depressive symptoms one year after being discharged [40]. This outcome was not consistent with a case-control study reporting sequelae 2.8 years following IMD.…”
Section: The Clinical Burden Of Imd In Francementioning
confidence: 74%
See 3 more Smart Citations
“…Higher rates (11.6%) were reported in adult cases with N. meningitidis purpura fulminans [47]. In the same way, a prospective observational study found that 34.3% of adult cases had depressive symptoms one year after being discharged [40]. This outcome was not consistent with a case-control study reporting sequelae 2.8 years following IMD.…”
Section: The Clinical Burden Of Imd In Francementioning
confidence: 74%
“…However, the available evidence is scarce. Only one observational study assessed the quality of life of adults survivors one year after the diagnosis, according to the research strategy of the present study [40]. Considering the patient's subjectively perceived wellness may improve the speed and quality of recovery from IMD [69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations